Why Spatial? Time and the Periphery. (2nd April 2016) - Vlachou, Foteini
Abstract : This article addresses a series of problems regarding the definition of the periphery in art history and its relation with the concepts of space and time. It seeks to disentangle the periphery from its geographical association by examining how it has instead been constructed as a primarily temporal concept. For this purpose, a tentative definition of the periphery is advanced based on the example of eighteenth-century Portugal. Also analysed is what can be termed as the delay discourse on the periphery (patent in several national historiographies of art, with Portugal serving again as an example), which was criticized by Carlo Ginzburg and Enrico Castelnuovo, as well as Nicos Hadjinicolaou already in the late 1970s and early 1980s. As a way out of the impasse of different or multiple temporalities (and the implication of fast and slow time) proposed by art historians from George Kubler to Keith Moxey, this article proposes the concept of historical time as developed in the writings of French philosopher Louis Althusser (1918–1990), in his analysis of Capital by Karl Marx (1818–1883), as a useful category in deconstructing the ideological dimension of periphery's temporal character. Rejecting both longue durée and a linear, ideological reference time, Althusser's terminology and concepts offer an incentive to think anew of time and the periphery, while insisting on the fundamentally unequal power configurations that have shaped both the practice of art history and a discourse on the periphery that continues, for the most part, to be produced in the centre(s).